Analisis Fiqh Kontemporer Terhadap Pernikahan Melalui Platform Digital: Studi Kasus Nikah Via Zoom - Hsb, Ummi Najipah; Khumairah, Jihan Oka; Hasibuan, Hazizah; Tami, Wilanda Juliani; Ananda, Aisah Putri (Albayan Journal of Islam and Muslim Societies, 2024)
Abstract The development of information technology has brought significant changes in the implementation of marriage contracts, one of which is the emergence of online marriage contracts through digital platforms such as Zoom. This study aims to analyse the validity of online marriage contracts from the perspective of contemporary fiqh. The method used is qualitative with a normative-theological approach through literature study. The results show that online marriage contracts can be considered valid as long as the pillars and conditions of marriage are fulfilled, such as the presence of the bride and groom, guardians, witnesses, and clear recitation of ijab and qabul in one virtual assembly. Some contemporary scholars and the more flexible Hanafi school support the validity of this contract. The contemporary fiqh approach also refers to maqashid sharia, which emphasises benefit and avoidance of hardship, making online marriage contracts a relevant solution in the digital era. The impact of this research shows that digital marriage contracts are a modern ijtihad that fulfils the needs of Muslims without ignoring the principles of sharia, provided that its application must be carried out carefully and responsibly.